Metode Analytical Hierarchy Process Dalam Menentukan Supplier WE Bakery - Agustina, Bella; Ramanda, Kresna; Rusman, Arief; Sikumbang, Erma Delima; Sukmana, Sulaeman Hadi (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Determining suppliers is important to support company performance, because determining the wrong supplier can cause harm to the company. Then the Analytical Hierarchy Process method is considered appropriate and appropriate for research related to problems in determining or selecting suppliers. By determining the right and optimal supplier using this AHP method, the company can select and evaluate suppliers so that the company can determine the appropriate criteria and alternative suppliers. Then the results are obtained that Arasari is considered the most appropriate to be a supplier with the highest weight gain priority of 0.427 or 42.7%, the second Lavanda Brownies of 0.291 or 29.1% and the third is Durian Orchid of 0.282 or 28.2%. While the results obtained through calculations using expert choice, explained that Arasari remained in first place with a value of 45.9% then Lavanda Brownies with a value of 29.7% and there was only a slight difference with Durian Orchid who obtained a percentage value of 24 4%. So based on these results, it can be seen that there is no difference in the order of global priorities for the total ranking goals obtained between manual data processing with the help of expert choice